Aus der Arbeit der Bibliothek des ehemaligen Deutschen Entomologischen Instituts. Nachlässe und Konvolute. - Marwinski, Felicitas (Contributions to Entomology = Beiträge zur Entomologie, 1975)
Further material from the archives of the library of the Department of Taxonomy of Insects (former Deutsches Entomologisches Institut) of the Institute of Plant Protection Research of the Academy of Agricultural Sciences of the GDR is made accessible with the papers left by L. von Heyden, L. Oldenberg and by the firm of Staudinger & Bang-Haas. Heyden left 9.770 letters and postcards from 735 correspondents written between 1856 and 1915, Oldenberg left 1.321 letters and postcards from 86 correspondents written between 1896 and 1931, and the papers of the firm of Staudinger & Bang-Haas 282 letters and postcards from 235 correspondents written between 1846 and 1923.